THE PSYCHOLOGICAL DISTRESS AMONG PATIENTS WITH CORONAVIRUS AFTER RECOVERING - Fatlawi, Duaa (PT. Antis International Publisher, 2026)
Objective: The Psychological Distress among Patients with Coronavirus after Recovering. Due to that public health emergencies resulting from COVID-19 are negatively impacting the mental health of the population affected by COVID pandemic. Method: A descriptive – analytic study Online sample that selected from Al Najaf Governorate from January 15th2021 through July 1st2021. Participants were invited to complete the GHQ-28 scale during the quarantine period. Results: A total of n = 199 surveys completed by patients with coronavirus. (53.77 %) of them have moderate levels according to the total score of 28-GH scale. And no significant relationship between demographic data and total 28-GH assessment. Novelty: The COVID-19 quarantine was associated with stresses and significant increases in symptoms of depression, anxiety, and stress in patients with coronavirus. The patients require increased access to mental health services to meet this increase in COVID-19-related psychological distress.